Association between periodontal inflammation and cognitive impairment among older adults: A clinical and biomarker-based study - Ramanarayana Boyapati (Bioinformation, 2026)
Cognitive impairment in older adults is influenced by chronic inflammatory exposures and periodontal inflammation may represent a modifiable contributor to systemic inflammatory burden. This clinical and biomarker-based cross-sectional study evaluated 180 adults aged 60 years and older using periodontal examination, periodontal inflamed surface area, Mini-Mental State Examination, Montreal Cognitive Assessment and serum inflammatory markers. Mild cognitive impairment was identified in 68 participants (37.8%) and these participants had significantly higher periodontal inflamed surface area (864 ą 318 mm2) than cognitively normal participants (523 ą 246 mm2; p